γδ T Cells in Immunity Induced by Mycobacterium bovis Bacillus Calmette-Guérin Vaccination - Lee, Jinhee (American Society for Microbiology, 2004)
Mycobacterium bovis bacillus Calmette-Guérin (BCG) vaccination is efficacious for newborns or adults with no previous exposure to environmental mycobacteria. To determine the relative contribution and the nature of γδ T-cell receptor-positive T cells in newborns, compared to CD4(+) T cells, in immunity induced by M. bovis BCG vaccination, 4-week-old specific-pathogen-free pigs were vaccinated with M. bovis BCG and monitored by following the γδ T-cell immune responses. A flow cytometry-based proliferation assay and intracellular staining for gamma interferon (IFN-γ) were used to examine γδ T-cell responses. Pigs were found to mount Th1-like responses to M. bovis BCG vaccination as determined by immunoproliferation and IFN-γ production. The γδ T-cell lymphoproliferation and IFN-γ production to stimulation with mycobacterial antigens were significantly enhanced by M. bovis BCG vaccination. The relative number of proliferating γδ T cells after stimulating peripheral blood mononuclear cells with Mycobacterium tuberculosis H37Rv culture filtrate protein was higher than that of CD4(+) T cells at an early time point after M. bovis BCG vaccination, but CD4(+) T cells were found to be more abundant at a later time point. Although the γδ T-cell responses were dependent on the presence of CD4(+) T cells for the cytokine interleukin-2, the enhanced γδ T cells were due to the intrinsic changes of γδ T cells caused by M. bovis BCG vaccination rather than being due solely to help from CD4(+) T cells. Our study shows that γδ T cells from pigs at early ages are functionally enhanced by M. bovis BCG vaccination and suggests an important role for this T-cell subset in acquired immunity conferred by M. bovis BCG vaccination.